2023
DOI: 10.3390/fishes8030137
|View full text |Cite
|
Sign up to set email alerts
|

Space and Time Use of European Eel Restocked in Upland Continental Freshwaters, a Long-Term Telemetry Study

Abstract: There is a lack of information on many biological and ecological aspects of the critically endangered European eel during its growth phase in inland waters, such as when the sedentary life stage begins, mobility according to age and response to habitat alteration. We used mobile radio frequency identification (RFID) telemetry technology to track tagged eels over 6 years after their restocking as glass eels in six typologically different rivers. We also cross-referenced telemetry data with those of several elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 56 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…These findings are consistent with the results presented here, suggesting that a shift to deeper and more lentic habitats as well as changes in substrate size preference with growth are common phenomena in anguillid eels. Such shifts may occur gradually, considering that Nzau Matondo et al (2023) recently reported that restocked Anguilla anguilla also gradually shifted to deeper habitats as they grow. However, these gradual shifts have not been sufficiently considered when evaluating their habitat use.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results presented here, suggesting that a shift to deeper and more lentic habitats as well as changes in substrate size preference with growth are common phenomena in anguillid eels. Such shifts may occur gradually, considering that Nzau Matondo et al (2023) recently reported that restocked Anguilla anguilla also gradually shifted to deeper habitats as they grow. However, these gradual shifts have not been sufficiently considered when evaluating their habitat use.…”
Section: Discussionmentioning
confidence: 99%
“…and a better understanding of the impact of invasive species on the local eel population from recruitment to spawning migration. For the future Eel Management Plan for the Neretva River Basin, which should have an international aspect (Bosnia and Herzegovina as a partner), several important actions should be proposed, such as research on current eel recruitment and potential increase of the glass eel population [28] to promote restoration of abundance in different habitats, a cooperative approach to local eel management, implementation of better fisheries and local market control, and improvement of available eel habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The study was carried out in Southern Belgium, in the six following upland rivers: Berwinne (A), Gueule (B), Wayai (C), Hoegne (D), Winamplanche (E) and Oxhe (F) (Figure 1). They belong to the Belgian Meuse River and were selected to receive glass eels on the basis of their typological difference on the hydromorphological, physicochemical and trophic levels, as described by our previous research [24,47]. The experimental sites were situated at a distance exceeding 320 km from the North Sea.…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, the glass eel stage is absent, and there is a drastic decline, if not total absence, of yellow eels [35,36,[50][51][52]. Rivers A and F are direct tributaries of the Meuse, alkaline, typical of the brown trout Salmo trutta fish zone, have a similar width and exhibit morphodynamic units of runs and rapids alternating with pools [24,47,53,54]. The occurrence of large stones (particle diameter 13-25 cm) and blocks (26-102 cm) is prevalent in eutrophic river A, whereas in oligotrophic river F, large and fine (6.4-12.8 cm) stones were found to be more frequent [54].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation